Thirty Years of Italian-Canadian Writing and the AICW - Zucchero, Jim (Italian Canadiana, 2020)
This essay offers an analysis of the past 30 years of activity in the Italian-Canadian literary community and examines the role of the AICW (Association of Italian-Canadian Writers) in supporting, disseminating and analyzing that literary production. It profiles the work of three important figures (Pivato, D’Alfonso, Di Cicco) and notes their contributions in establishing this literary ground. It also asserts that women have played an essential role, both in their literary contributions, and in organizational capacities (editing anthologies and proceedings, organizing and promoting literary events and conferences). The essay considers practical issues (developments in technology), challenges, and the vital relationship between creative works and literary criticism in this body of writing.